Deployment of Docker Services on Private Cloud (International Journal of Innovative Research in Computer Science & Technology, 2018)
The proposed paper presents the topic  “Deployment of Docker Services on Private Cloud”. It  briefs how the system is implemented to provide Docker  services to client, in order to reduce client’s overall  system load and to make the client enjoy the application  layer facilities easily. The paper tells how this system  uses Docker Hub which works on the concept of  Container as a Service, thus making the task of  creating, deploying and running applications simpler  and light weighted. Docker Server in this system acts as  a bridge between Docker client and Docker Hub. Client  requests server for applications, server fetches the  images from Docker Hub via Docker Engine which is  responsible for packing these images along with its  dependencies and binaries into a Container. Client can  access these applications using web browser  (URL,Tags). Traditionally, server could access Docker  through Command Line Interface (CLI); hence to make  it simpler, we present this paper illustrating creation of  User Interface (UI) for the server side. Thus this paper  summarizes how Docker services are deployed on  private cloud
Keywords: Cloud; Docker; Container.